2010
DOI: 10.1063/1.3393960
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of granular CoCrPt:SiO2 films as tailored by Co+ irradiation

Abstract: Articles you may be interested inSuccessful fabrication of high K u columnar CoPt-SiO2 granular film sputtered under high substrate temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…By using magnetic ions, we can directly influence the intergranular exchange by introducing Co atoms into the grain boundaries, which allows us to tailor the magnetic exchange coupling between CoCrPt grains in a controlled manner [65]. In particular, we found that irradiation at low fluences results in the increase of the exchange coupling leading to a substantial increase of the remanent magnetization.…”
Section: Granular Cocrpt-sio 2 Alloy Films On Sio 2 Particle Arraysmentioning
confidence: 83%
“…By using magnetic ions, we can directly influence the intergranular exchange by introducing Co atoms into the grain boundaries, which allows us to tailor the magnetic exchange coupling between CoCrPt grains in a controlled manner [65]. In particular, we found that irradiation at low fluences results in the increase of the exchange coupling leading to a substantial increase of the remanent magnetization.…”
Section: Granular Cocrpt-sio 2 Alloy Films On Sio 2 Particle Arraysmentioning
confidence: 83%
“…The observed feather-like domains can be explained based on the IP magnetization distribution and transport of the magnetic charge toward the surface, which is achieved by a small deviation from the IP magnetization, similar to the formation of cross-tie walls . The modified domain morphologies can be different for different material systems and choice of ions . The surface roughness of the films increases with higher ion energy, and the fragmented maze-like domains could not be observed for the irradiated samples with E = 100 keV; the corresponding AFM and MFM images are presented in Figure S2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“… 62 The modified domain morphologies can be different for different material systems and choice of ions. 63 The surface roughness of the films increases with higher ion energy, and the fragmented maze-like domains could not be observed for the irradiated samples with E = 100 keV; the corresponding AFM and MFM images are presented in Figure S2 of the Supporting Information . Thus, variation in the domain size and pattern can be tuned via locally competing anisotropies, which create a strong force for the SRT toward the IP direction.…”
Section: Resultsmentioning
confidence: 99%
“…Ga, He and Ar [7,[22][23][24][25][26], or magnetic ion specimens, i.e. Co [27], was recently introduced.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we demonstrate the possibility to tune the magnetic properties of CoCrPt:SiO 2 films grown on selfassembled arrays of SiO 2 spherical particles using irradiation with magnetic Co + ions. By using magnetic ions, we can directly influence the intergranular exchange by introducing Co atoms into the grain boundaries, which allows us to tailor the magnetic exchange coupling between CoCrPt grains in a controlled manner [27], thus influencing the integral magnetic properties, i.e. remanence magnetization, coercive field and magnetic domain configuration.…”
Section: Introductionmentioning
confidence: 99%